The ASCEND-ND trial: study design and participant characteristics. Issue 11 (2nd December 2021) - Perkovic, Vlado; Blackorby, Allison; Cizman, Borut; Carroll, Kevin; Cobitz, Alexander R; Davies, Rich; DiMino, Tara L; Jha, Vivekanand; Johansen, Kirsten L; Lopes, Renato D; Kler, Lata; Macdougall, Iain C; et al.
ABSTRACT: Background: Anaemia is common in chronic kidney disease (CKD) and assessment of the risks and benefits of new therapies is important. Methods: The Anaemia Study in CKD: Erythropoiesis via a Novel prolyl hydroxylase inhibitor Daprodustat-Non-Dialysis (ASCEND-ND) trial includes adult patients with CKD Stages 3–5, not using erythropoiesis-stimulating agents (ESAs) with screening haemoglobin (Hb) 8–10 g/dL or receiving ESAs with screening Hb of 8–12 g/dL. Participants were randomized to daprodustat or darbepoetin alfa (1:1) in an open-label trial (steering committee- and sponsor-blinded), with blinded endpoint assessment. The co-primary endpoints are mean change in Hb between baseline and evaluation period (average over Weeks 28–52) and time to first adjudicated major adverse cardiovascular (CV) event. Baseline characteristics were compared with those of participants in similar anaemia trials. Results: Overall, 3872 patients were randomized from 39 countries (median age 67 years, 56% female, 56% White, 27% Asian and 10% Black). The median baseline Hb was 9.9 g/dL, blood pressure was 135/74 mmHg and estimated glomerular filtration rate was 18 mL/min/1.73 m 2 . Among randomized patients, 53% were ESA non-users, 57% had diabetes and 37% had a history of CV disease. At baseline, 61% of participants were using renin–angiotensin system blockers, 55% were taking statins and 49% were taking oral iron. Baseline demographics were similar to those in other large non-dialysis anaemia trials. Conclusion: ASCEND-ND will define the efficacy and safety of daprodustat compared with darbepoetin alfa in the treatment of patients with anaemia associated with CKD not on dialysis. Graphical Abstract: